A new genus of Cruciferae (Brassicaceae) from the State of Guerrero, Mexico - Diego Pérez, Nelly; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2004)
Lexarzanthe is proposed as a new genus of the Cruciferae on the basis of Romanschulzia mexicana, a species originally described from fruiting material collected in the Mexican state of Guerrero. Recent collections of the same plant obtained in flowering condition reveal that this species differs from Romanschulzia in its ample corymbiform inflorescence with long and slender pedicels, in its much larger flowers with erect sepals and petals which persist during anthesis, as well as in its notably exserted stamens. In view of these differences the plant should be placed in a separate genus, which also belongs in the tribe Thelypodieae, but seems to be more closely related to Warea and Stanleya, genera considered as primitive in the family.